Molar Conductivity Behaviour of LiClO4 in Poly(ethylene oxide) Solutions - Hanibah1, Hussein; Ahmad1, Azizan; Hasyareeda Hassan1, Nur (Asian Journal of Chemistry, 2014)
This article presents a study of the molar conductivity (L0) behaviour of LiClO4 in PEOX solutions at 25 °C. The specific conductivity (k) of the electrolyte systems were studied as a function of lithium salt concentration (Csalt), polymer concentration (CPoly) and molecular weight (Mh). The electrolyte system of poly(ethylene oxide) (PEOX) (Mh = 600, 1,000 and 4,000 Kg mol-1) in acetonitrile has been prepared in a range of 0.0010-0.0030 g cm-3, respectively was used as solvents to dissolved lithium perchlorate (LiClO4). The k of PEOX solutions, has been measured as a function of Csalt at 25.0 °C using AC conductivity meter. The L0, equilibrium constant (Keq) and critical ion-pairs concentration (b) for LiClO4 in PEOX solutions at different CPoly and molecular weight were determined after Ostwald's dilution law. It was noticed, as PEOX concentration increased the L0 value showed a decreasing trend, indicated the change of solvent properties to a better electrolyte system relative to LiClO4 in acetonitrile (176.68 S cm2 mol-1) with an acceptable small error. This decreasing trend of L0 gives a significant improvement in the total LiClO4 dissociation particularly at higher PEOX concentration in the electrolyte system. This been noticed with a much lower Keq values relative to LiClO4 in acetonitrile system at 25 °C. A similar observation was also noted for higher Mh PEOX solutions. However, from b calculation it is noted that the low molecular PEOX at lower CPoly act as a better electrolyte compare to higher molecular PEOX and a vice versa observation is noted at higher CPoly. In conclusion, the addition of PEOX into the LiClO4 solution leads to the decreases of the L0 value and enhances LiClO4 dissociation particularly for higher PEOX concentration at higher Mh. This might due to changes in its viscosity of the solution that interrelated with the Walden rule.